Coral disease on fungiidae at Sop Island, Sorong, Papua Barat. Issue 1 (1st June 2022) - Subhan, Beginer; Rahmawati, Fadhilah; Arafat, Dondy; Bramandito, Aditya; Khairudi, Denny; Royhan, Q Muhammad; Madduppa, Hawis; Santoso, Hendi; Fauzi, Firli Rahman Hakim; Revany, Retia; Wiyanto, Dwi Budi; Prehadi,; et al.
Abstract: This research is located at Sop Island, Sorong, West Papua. The data was collected using the Belt Transect method, stretching a line for 50 meters with a width of vision for 2.5 meters to the left and 2.5 meters to the right. The depth of the transect is 5 meters, recorded all genera from Family Fungiidae. Five genera were found on The Sop Island, namely Ctenactis, Fungia, Herpolitha, Polyphyllia, and Sandalolitha, but only Ctenactis, Fungia, and Sandalolitha were found on the three sites of observation. Fungia is the most abundant genera found at Sop Island. So, however, the study also found many unhealthy symptoms that infected Fungia . Of the three observation sites, six categories of unhealthy coral are found: Tissue Loss - non-predation - Coloured Band Disease, Tissue Discoloration - White, Tissue Discoloration non-white, Compromised Health Growth Anomalies, and Unknown. The most common categories infected with the Fungiidae at Sop Island are Tissue Loss - non-predation - Coloured Band Disease, Tissue Discoloration - White. Agonizingly, researchers found coral disease at every site.